The Knowledge Exchange and Marketing Strategies to Enhance the Management Potential of Restaurant Entrepreneurs in Bangkok - Khumbamrung, Suparat; Niamsorn, Chawalin; Tongprasong, Phorramatpanyaprat (Rajapark Journal, 2024)
This research aims to study the factors of knowledge exchange and marketing strategies that influence the management potential of restaurant entrepreneurs. This research used quantitative research. The questionnaire was used to collect data. The sample group consists of 347 restaurant entrepreneurs in Bangkok. They were analyzed with frequency, percentage, Influence path analysis, and the structural equation model (SEM). The results found that the factors of knowledge exchange and marketing strategies on the management potential of restaurant entrepreneurs are consistent with the empirical data, including the Chi-square value (χ2) of 53.247, df = 41, p-value = 0.095, Chi-square/df = 1.299, CFI = 0.997, GFI = 0.974, AGFI = 0.951, RMSEA = 0.029, RMR = 0.008, and NFI = 0.986. The results indicate that knowledge exchange positively affected the management potential of restaurant entrepreneurs with a path coefficient of 0.282. Additionally, knowledge exchange positively affected the marketing strategy of restaurant entrepreneurs with a path coefficient of 0.861. The marketing strategy positively affected the management potential of restaurant entrepreneurs with a path coefficient of 0.733. Knowledge exchange affected the management potential of restaurant entrepreneurs through a group of marketing strategy variables with a path coefficient of 0.913. Restaurant entrepreneurs should prioritize knowledge exchange to obtain information supporting the management of their restaurants and focus on marketing strategies that meet target customers' needs to improve the quality of restaurant management.